PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arrosyida, Via; Khoiriawati, Novi (Bilancia : Jurnal Ilmiah Akuntansi, 2023)
ABSTRACT This study aim to examines and analyze the effect of financial performance that is projected with financial ratios in the form of quick ratio (QR), total asset turnover (TATO), net profit margin (NPM), earning per share (EPS), price to earning ratio (PER), and price to book value (PBV) on stock price. The type of research used is quantitative asosiatif research. Data collection technic used is documents review. The data source derived from secondary data of annual financial report and annual closing price of stock. The population of this study is healthcare sector companies listed on the Indonesian Stock Exchange totaling 24 companies. 50 samples in this study were selected by purposive sampling method and analyzed using panel data regression. The result showed that QR, TATO, and NPM had no positive significant effect on stock price, EPS and PER had positive land no significant effect on stock price, while PBV had positive significant effect on stock price. The study result imply that investors of healthcare sector companies listed on the Indonesian Stock Exchangenot not paying attention to QR, TATO, NPM, EPS, PER, except PBV in terms of making decision to buy stock price. Keywords: Stock Price, Financial Performance, Financial Ratio